Using Chinese as L1 in Secondary English as a Foreign Language Classrooms: Does it Matter? - Ester de Jong; Jing Zhang (Cranmore Publishing, 2021)
Whether L1 (the first language) should be used in English (as the second or foreign language) classrooms has long been a controversial issue. In the United States, much of this work has focused on French or Spanish as a foreign language teaching and learning. In the context of English as a foreign language, research has focused on adults and primary school students. This literature review considers this question in the context of Chinese as L1 and secondary EFL classrooms. Our review suggests that the use of Chinese serves several supportive functions and that, despite the insistence on strong English-only policies, teachers and students actively use Chinese to enhance their language teaching and learning experiences.